Fast response GTO assisted novel tap changer. - Hao Jiang (IEEE Transactions on power delivery)
A new type of GTO thyristor assisted tap changer is outlined which addresses the problems of traditional schemes. The scheme minimizes conduction losses in the solid state devices and also permits a fast response speed through the adoption of fast actuator driven vacuum switches. This paper describes a prototype tap changer for a low voltage 300 kVA transformer using the new method of tap changing. The prototype operates at current levels similar to those at which a full scale tap changer would work. Test results are presented